ORAL III GENERATION CEPHALOSPORIN CEFTIBUTEN IN TREATMENT OF ACUTE TONSILLOPHARYNGITIS AND OTITIS - S. A Karpishchenko; E. B. Katinas; N. A. Shumilova ("Paediatrician" Publishers LLC, 2012)
Tonsillopharyngitis is a common multietiological infectious disease, more often caused by streptococci infection. The development and adoption of oral III generation cephalosporins into clinical practice significantly widened the possibilities of treatment of inflammatoryinfectious diseases, including tonsillopharyngitis. One of the III generation cephalosporins is Ceftibuten (Cedax) - a drug with b-lactam properties, which inhibits bacterial peptidoglycan synthesis. It has relatively long post-antibiotic effect, characterized by high activity in point of majority of enterobacteria, and is very stable to destructive action of -lactamases. It also can be accumulated in tissues, providing high concentration of active substance in inflammation nidus. The therapeutic dose of the drug for adults is 400 mg/day. Ceftibuten is recommended and effectively used in pediatric practice in treatment of tonsillopharyngitis and otitis.